Pedagogical resources and content of alphabet and reading books in the context of patriotic education of younger schoolchildren - Khrystyna Bedrii (Vasyl Stefanyk Precarpathian National University, 2017)
The article is devoted to the actual theme - that is the patriotic education of the studentsof the primary school and the analysis of the pedagogical contain of bukvar and chytanka asthe first textbooks that create children`s imagination about the outworld. Key words: patriotic education, primary school, primary school students, textbooks,bukvar, chytanka.